A New Approach for Robot-assisted Left Upper Lobectomy: Single-Directional via Interlobar Fissure - Lu, Rui; Cheng, Nitao; Tao, Xi; Liu, Jun; Hu, Weidong (The Surgery Journal, 2025)
With the introduction of robot-assisted thoracoscopic surgery (RATS), many lung surgeries can be well exposed and completed. However, the removal of the upper lobe of the left lung still puzzles many clinicians because of its anatomical characteristics, especially in patients with large tumors and difficult flip of lung lobes, or patients with enlarged lymph nodes or portal nail lymph nodes. In this article, we introduce a new surgical approach, namely, “single-directional lobectomy via interlobar fissure (SDLIF),” for the rapid and safe removal of the left upper lung under RATS.We retrospectively analyzed 35 patients who underwent left upper lobectomy for lung cancer using SDLIF approach under Da Vinci RATS. We counted the following indicators such as the operation time, intraoperative bleeding, number of lymph node dissection, incidence of postoperative lung air leakage, postoperative hospital stay, tumor types, pathological stages, resection completeness, and other complications.With this surgical method, all patients were successfully operated without serious complications. This procedure reduced the amount of high-value consumables used and decreased the operation time. Besides, compared with a previous study, it reduced the amount of intraoperative blood loss.SDLIF is a simple, easy-to-learn, fast and safe lobectomy, which is especially suitable for patients with large tumors and difficult flip of lung lobes, or patients with enlarged lymph nodes or portal nail lymph nodes, and is a surgical technique worth promoting and spreading.
Keywords: surgical approach; left upper lobectomy; robot-assisted; single-directional; interlobar fissure